2015
DOI: 10.1016/j.ygcen.2015.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Advanced seasonal reproductive development in a male urban bird is reflected in earlier plasma luteinizing hormone rise but not energetic status

Abstract: Urban animals inhabit an environment considerably different than do their non-urban conspecifics, and to persist urban animals must adjust to these novel environments. The timing of seasonal reproductive development (i.e., growth of gonads and secondary sex organs) is a fundamental determinant of the breeding period and is frequently advanced in urban bird populations. However, the underlying mechanism(s) by which birds adjust the timing of reproductive development to urban areas remain(s) largely unknown. Her… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
18
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 53 publications
4
18
3
Order By: Relevance
“…Urban Abert's Towhees increased plasma LH, but not plasma testosterone, earlier than non-urban birds (Davies et al, 2015). In our captive common-garden, sedentary urban and migrant juncos also had similar plasma testosterone in the first 2 weeks of comparison, but diverged in the final 2 weeks of our study, with sedentary juncos displaying elevated baseline testosterone levels.…”
Section: Discussionsupporting
confidence: 41%
See 1 more Smart Citation
“…Urban Abert's Towhees increased plasma LH, but not plasma testosterone, earlier than non-urban birds (Davies et al, 2015). In our captive common-garden, sedentary urban and migrant juncos also had similar plasma testosterone in the first 2 weeks of comparison, but diverged in the final 2 weeks of our study, with sedentary juncos displaying elevated baseline testosterone levels.…”
Section: Discussionsupporting
confidence: 41%
“…To date, there is limited evidence from studies that have compared the endocrine axes of urban vs. nearby rural populations in both field and common garden settings to support the importance of both plasticity and genetics in modulating earlier reproduction and HPG activation in urban habitats (Partecke et al, 2004(Partecke et al, , 2006Schoech, 2009;Atwell et al, 2014;Davies et al, 2015). While these studies highlight the importance of differential HPG activity in facilitating earlier and extended breeding in urban habitats, much remains to be learned about the generality of those results, as well as the specific mechanistic sources of variation across the many "levels" of the HPG axis.…”
Section: Introductionmentioning
confidence: 99%
“…,Ausprey & Rodewald (2011),Stracey & Robinson (2012),Varner et al (2014),Evans, Ryder, Reitsma, Hurlbert, & Marra (2015),Rebolo-Ifran et al (2015),Minias (. (2008),Chavez-Zichinelli et al (2010),Davies et al (2015),Audet et al , & Hudelson (1998),Fokidis et al (2008),Geue & Partecke (2008),Bichet et al (2013),Jacquin et al (2013),,Delgado & French (2015),Bentz et al , Heeb, & Cezilly (2002),Evans, Gaston, Sharp, Mcgowan, Simeoni, et al , & Andersson (2005),Skarphedinsdottir et al (2010),,,Herrera-Duenas et al (2014),Giraudeau et al , Ots, & Møller (2004),Isaksson et al (2005),Isaksson, Mclaughlin, et al (2007),Isaksson, Von Post, et al (2007),,Grunst, Rotenberry, & Grunst (2014),, Giraudeau et al (2015), Herrera-Duenas et al (2014), Hõrak et al . (2008), Liker et al (2008), Evans, Evans, Gaston, Sharp, Mcgowan, Hatchwell, et al (2009), Fokidis, Hurley, Rogowski, Sweazea, & Deviche (2011), Seress et al (2011), Giraudeau et al (2015), Meillere et al (2015), Audet et al , Novoa, & Sabat (2002), Auman et al (2008), Liker et al (2008), Evans, Gaston, Sharp, Mcgowan, Hatchwell, et al (2009), Fokidis et al (2011), Seress et al (2011), Davies, Rodriguez, Sweazea, & Deviche (2013), Giraudeau & Mcgraw (2014), Giraudeau et al (2015), Meillere et al (2015), Audet et al Post, et al (2007), Auman et al (2008), Fokidis et al (2008), Liker et al (2008), Jones, Rodewald, & Shustack (2010), Seress et al (2011), Bokony, Seress, et al (2012), Bichet et al (2013), Cardilini, Weston, Nimmo, Dann, & Sherman (2013), Davies et al (2013), Jacquin et al (2013), Morrissey et al (2014), Meillere et al (2015), Audet et al (2016), Minias (.…”
mentioning
confidence: 99%
“…Two persons independently scored the plates blind to sample identity. We previously showed that their lysis and agglutination scores were highly repeatable for both agglutination and lysis (Davies et al, 2015).…”
Section: Agglutination and Lysis Assaymentioning
confidence: 99%